Sufi Movements on British Anti-Colonial Resistance in Bengal of Indian Subcontinent: A Study of Religious and Political Intersections - Chowdury, Saeyd Rashed Hasan; Chowdury, Saeyd Rashed Hasan (Ataturk Univ, 2025)
This article critically examines the resistance movements initiated and led by Sufi leaders against British colonial rule in the Bengal region of the Indian subcontinent, focusing on present-day Bangladesh and the Indian states of West Bengal, Tripura, and Assam. The study highlights significant historical events such as the Fakir Rebellion (1765), the Battle of Balakot led by Sayyid Ahmed Barelvi, the Bamboo Fort Movement led by Titu Mir, the Faraizi Movement initiated by Haji Shariatullah, and the Khilafat Movement, which aimed to protect the Ottoman Caliphate and resist British imperialism. It analyses the multifaceted resistance strategies employed by Sufi leaders in response to British imperial oppression. British colonial control in Bengal commenced with the defeat of Nawab Siraj-ud-Daulah at the Battle of Plassey in 1757 and lasted until the subcontinent's partition in 1947. During this period, Bengal's Muslim population faced significant social, cultural, and religious repression under colonial rule. Sufi leaders played an essential role in mobilising the Bengali Muslim community around the concept of Ummah, organising a formidable resistance against colonial authorities. This study employs qualitative research methods, exploring the Sufi movement's resistance to British colonialism in Bengal and focusing on its influence on the Muslim community's political and cultural identity formation.
Sufi Movements on British Anti-Colonial Resistance in Bengal of Indian Subcontinent: A Study of Religious and Political Intersections
Keywords: Sufism; Indian Subcontinent; Bengal; British Colonial Rule; Resistance Movements